The legend of Sleepy Hollow, and Rip Van Winkle - Irving, Washington 1783-1859 (Great illustrated classics, 1995)
In the first of these stories from the Catskill Mountains, a superstitious schoolmaster encounters a headless horseman; in the second, a man sleeps for twenty years, waking to a much-changed world.